2017
DOI: 10.1111/birt.12295
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between cesarean birth and stress, anxiety, and depression after childbirth: A nationwide cohort study

Abstract: Cesarean birth was associated with an increased risk of postpartum stress symptoms. Health professionals should avoid unnecessary cesarean birth, pay attention to women who deliver by cesarean, and intervene appropriately in an attempt to improve mental health among postpartum women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
2
36
1
4
Order By: Relevance
“…Some other evidence-based studies also showed the same ndings about the relationship between the type of delivery and postpartum depression [4][5][6]. However, some researchers pointed out that there was no obvious association between mode of delivery and maternal postpartum psychiatric disorders [7][8].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Some other evidence-based studies also showed the same ndings about the relationship between the type of delivery and postpartum depression [4][5][6]. However, some researchers pointed out that there was no obvious association between mode of delivery and maternal postpartum psychiatric disorders [7][8].…”
Section: Introductionmentioning
confidence: 76%
“…The study by Ri-hua Xie et al included 415 patients with CS, 119 patients with VD [7]. The study by Hung-Hui Chen et al included 12619 patients with CS, 12619 control subjects [8]. The study by Vincenzo Zanardo et al included 256 patients with CS and 694 control subjects [11].…”
Section: Association Between Delivery Mode and Postpartum Depressionmentioning
confidence: 99%
“…Similarly, Chen et al 28 nationwide study in Taiwan revealed that cesarean birth was not a factor of PPD but was for symptoms of stress. 28 Although Shelton and Cormier 2 reported that cesarean delivery might be a predictor for PPD, different studies have shown otherwise. 2 A recent review reported that the presence of depressive symptoms in the third trimester was an independent predictor of emergency cesarean delivery.…”
Section: Discussionmentioning
confidence: 93%
“…However, type of delivery was not associated with PPD in the current study sample. Similarly, Chen et al nationwide study in Taiwan revealed that cesarean birth was not a factor of PPD but was for symptoms of stress . Although Shelton and Cormier reported that cesarean delivery might be a predictor for PPD, different studies have shown otherwise .…”
Section: Discussionmentioning
confidence: 98%
“…The study by Ri-hua Xie et al included 415 patients with CS, 119 patients with VD [7]. The study by Hung-Hui Chen et al included 12619 patients with CS, 12619 control subjects [8]. The study by Vincenzo Zanardo et al…”
Section: Association Between Delivery Mode and Postpartum Depressionmentioning
confidence: 99%